Cytoplasmic Tail Phosphorylation of the α-Factor Receptor Is Required for Its Ubiquitination and Internalization - Hicke, Linda (The Rockefeller University Press, 1998)
G protein–coupled (GPC) receptors are phosphorylated in response to ligand binding, a modification that promotes receptor desensitization or downregulation. The α-factor pheromone receptor (Ste2p) of Saccharomyces cerevisiae is a GPC receptor that is hyperphosphorylated and ubiquitinated upon binding α-factor. Ubiquitination triggers Ste2p internalization into the endocytic pathway. Here we demonstrate that phosphorylation of Ste2p promotes downregulation by positively regulating ubiquitination and internalization. Serines and a lysine are essential elements of the Ste2p SINNDAKSS internalization signal that can mediate both constitutive and ligand-stimulated endocytosis. The SINNDAKSS serines are required for receptor phosphorylation which, in turn, facilitates ubiquitination of the neighboring lysine. Constitutive phosphorylation is required to promote constitutive internalization, and is also a prerequisite for ligand-induced phosphorylation at or near the SINNDAKSS sequence. Mutants defective in yeast casein kinase I homologues are unable to internalize α-factor, and do not phosphorylate or ubiquitinate the receptor, indicating that these kinases play a direct or indirect role in phosphorylating the receptor. Finally, we provide evidence that the primary function of phosphorylation controlled by the SINNDAKSS sequence is to trigger receptor internalization, demonstrating that phosphorylation-dependent endocytosis is an important mechanism for the downregulation of GPC receptor activity.